Determination of Iron (II) in Aqueous Solutions Using Organic Reagent 3-Hydroxy-4-[ (2-hydroxy benzylidene) amino] naphthalene-1- Sulphonic Acid by Spectrophotometric Method (Latakia University Journal -Basic Sciences Series, 2025)
The possibility of formatting a colored complex between Fe2+ ions and 3-Hydroxy-4-[ (2-hydroxy benzylidene) amino] naphthalene-1- Sulphonic Acid was studied by spectrophotometric method for determination of Iron in aqueous solutions. The reagent reacts in aqueous medium at pH=6 to give an Yellow complex with maximum absorbance at λmax=420nm. The stoichiometric composition of complex is (1:2). The molar absorptivity and complex constant formation were found to be ε=1.1013×105 l. mol-1.cm-1 and βk =0.4985×103. We have studied all factors which affect the complex formation. Beer-Lambert was obeyed within the range (0.1-6) mg/l with a detection limit of 0.0643 mg/l. The developed method was examined on Iron standard solutions, and the Relative Standard Deviation is  (RSD%≤3.33), and the recovery ( 92-102.5 )%. All results showed the accuracy, reliability and confirming the possibility of  using the reagent to determination of Iron.